As relações étnico-raciais na experiência cineclubista escolar - Porto, Rosana Almeida (2024)
This study sought to investigate how a student film club experience can contribute to the study of ethnic-racial relations. To this end, we adopted a perspective of cinema as art in school and capable of promoting alterity, as proposed by Bergala (2008). The research was carried out in a state public school in Goiânia-GO, with students from the 6th to 9th year of primary school. For this qualitative action-research, a bibliographical review was initially carried out on the subject of race, using theorists who deal with the racial issue. Empirical research was also carried out using participant observation. The activities developed were: film screenings, discussions and analyses of the themes addressed in the works, film exercises and audiovisual production with the students. These activities culminated in the creation of a script as an educational product of the activities carried out, entitled "Script for film club experiences", available at the end of this dissertation. This pedagogical proposal for teaching ethnic-racial relations was developed during the Professional Master's in Teaching in Basic Education of the Stricto Sensu Postgraduate Programme at CEPAE/UFG. The product was implemented and experienced at the school and the results can be accessed on the YouTube channel called "Film club experiences at school". This channel presents the results obtained after the implementation of a participatory pedagogical intervention, which was carried out based on the proposal by Bergala (2008), Migliorini (2015), Fresquet (2013) and Albuquerque (2022). The results were significant and made it possible to build important knowledge about ethnic-racial issues, as well as stimulating the students' creativity and protagonism.